The neurobiology of consciousness - Koch, Christof (Henry Stewart Talks, 2010)
The mantra of the science of consciousness, What do we know about consciousness?, Content of consciousness must be distinguished from states of consciousness, Ascending reticular activating system, Pathologies in states of consciousness, When does consciousness begin?, Consciousness in non-human animals, What do we not know about consciousness?, Neural correlates and consciousness, Consciousness and planning, V1 activity, Attention and consciousness, The human medial temporal lobe, The effect of masking on neurons, The need to move from correlation to causation